1 | initial version |

You can try something like this (with `x`

and `y`

as variables and `z`

as parameter):

```
sage: var('x y z')
(x, y, z)
sage: f(x,y) = x*y*z
sage: f.hessian()
[(x, y) |--> 0 (x, y) |--> z]
[(x, y) |--> z (x, y) |--> 0]
```

2 | No.2 Revision |

You can try something like this (with `x`

and `y`

as variables and `z`

as parameter):

```
sage: var('x y z')
(x, y, z)
sage: f(x,y) = x*y*z
sage: f.arguments()
(x, y)
sage: f.variables()
(x, y, z)
sage: f.hessian()
[(x, y) |--> 0 (x, y) |--> z]
[(x, y) |--> z (x, y) |--> 0]
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.